CRITICAL ANALYSIS OF REALIBILITY OF THE MODEL OF INVESTMENT CREDIT APPROVAL IN AGRICULTURE AND FOOD PROCESSING INDUSTRY - Barjaktarović, Lidija; Pindzo, Renata; Hanić, Azra (Economics of Agriculture, 2016)
Investments are funds which are invested in certain manufacturing goods, revenue on investments, the process of investment, subject in which it is invested, and which is obtained as a result of the assessment of investment. Every rational investor entering into an investment expects some benefts. Entry decision into a particular investment project carries a business risk, both for investors and for the bank as co-fnancier of the project. Accordingly, the subject of this paper-research is a critical analysis of the reliability of the model of investment credit approval in agriculture and food processing industry (MICA) used by local banks when considering whether to fnancially support investment needs of large corporate customers in the segment of secondary agriculture production and food processing industry. Applying the model of the correlation analysis, the degree of interconnectedness of indicators of the quality of assets and business performances of Serbian banking sector are quantifed.